Evaluación de enfermedades fungosas del arbolado urbano de los parques y avenidas de la ciudad de Loja - Armijos Díaz, Josué David (2023)
The study of green areas is of particular importance in the current context of climate change and conservation of nature. They can provide environmental benefits and services that improve urban welfare and improve environmental quality. Urban trees that are located in parks and avenues offer scenic beauty and environmental benefits in Loja; however, silvicultural management is limited, resulting in limited development of plant species on a morphological and physiological level, which can lead to phytosanitary problems, particularly fungal diseases. Research is conducted in the field of plant health in evaluating the symptomatology and determining the causal agent of fungal diseases present in urban trees. The methodology applied was qualitative - descriptive. In the field the six most abundant species in parks and avenues were evaluated, considering 30% of individuals for each species as a representative sample, affected parts of the tree were collected and taken to the laboratory for isolation and identification of the pathogen. Symptoms were determined as: necrosis, affecting mainly Chionanthus pubescens; Morus alba; Eriobotrya japonica, with the causal agent Alternaria sp; white powder on Leucaena leucocephala, with the causal agent Oidium sp; yellowing on Morus alba, with the causal agent Fusarium sp; yellow spots with brown pustules on Chionanthus pubescens, with the causal agent Melampsoridioum sp; blackish scab on Sapindus saponaria, with the causal agent Capnodium sp; and finally torque on Morus alba, with the causal agent Taphrina deformans. In terms of symptoms and causal agents, necrosis (Alternaria sp) and white powder (Oidium sp) topped the list; and Morus alba and Chionanthus pubescens showed the greatest frequency of symptoms. In view of this, it would be important to implement a management plan for the phytosanitary status of the trees, in addition to using native plants for urban tree planting.